Use of Z-codes related to social determinants of health among adult inpatients in France: a nationwide study from 2014 to 2022 - Sara Fernandes; Vanessa Pauly; Sophie Klay; Veronica Orleans; Yann Brousse; Bach Tran; Masoud Rahmati; Dong Keon Yon; Lee Smith; Guillaume Fond; Coralie Lemoine; Francois Antonini; et al. (BMC Public Health)
Abstract Background Health is shaped by a complex network of socio-economic, environmental and behavioral factors, known as social determinants of health (SDOH). SDOH can be optionally documented using Z codes from the International Classification of Diseases, Tenth Revision (ICD-10) in the French national hospital database. This study aimed to (a) describe the use of SDOH codes among adult inpatients in France in 2022, and temporal trends from 2014 to 2022; and (b) identify the characteristics of hospital stays associated with the presence of SDOH codes. Methods We conducted a nationwide retrospective, cross-sectional, observational study using the French national hospital database. All stays for patients aged 18 years or older in acute care hospitals between 2014 and 2022 were included. The outcome was the presence of at least one SDOH code (Z55-Z75). Temporal trends in the use of SDOH codes from 2014 to 2022 were analyzed using univariable linear regression. Univariable and multivariable mixed-effects models were used to identify characteristics of hospital stays associated with SDOH codes for the year 2022. Results From 2014 to 2022, 83,741,127 stays were identified, of which 6,321,390 (7.6%) had at least one SDOH code. Among 8.6 million hospital stays in 2022, 9.4% included an SDOH code, primarily documenting social conditions (6.5%), environmental (2.5%), and economic housing (1.2%) domains. There was an increase in the reporting SDOH codes from 2014 (5.0%) to 2022 (9.4%). In the multivariable analysis, the presence of at least one SDOH code was associated with female sex (adjusted odds ratio (aOR = 1.34, 95%CI [1.33;1.34]), being aged 65–74 years (aOR = 1.26 [1.25;1.28]) or older (aOR = 2.25 [2.40;2.45]) compared with the 18–34 age group, receiving social assistance, particularly state medical assistance (aOR = 4. 02 [3.93;4.11]), having comorbidities (1–2: aOR = 1.44 [1.43;1.45]; ≥3: aOR = 1.70 [1.69;1.71]), mental disorders (aOR = 3.44 [3.40;3.49]), and hospitalization in public hospitals, especially non-academic public hospitals (aOR = 7.19 [7.01;7.38]). Conclusion Despite the observed increase in SDOH coding between 2014 and 2022, our study suggests that their use remains limited in France. These findings highlight the need for a national strategy to promote systematic SDOH documentation and their integration into care, supported by adequate funding, ultimately fostering more equitable healthcare delivery that integrates medical and social needs into clinical practice.